MANAJEMEN PESERTA DIDIK DALAM MEMBENTUK KEDISIPLINAN SANTRI DI PONDOK PESANTREN BUSRA CHALID - Isnani Nazwatunissa; Ahmadi Ahmadi; Nurul Hikmah (STKIP Pesisir Selatan, 2026)
This study aims to analyze student management in shaping students’ discipline at Busra Chalid Islamic Boarding School in Palangka Raya and is expected to serve as a reference for other Islamic boarding schools. The research employed a qualitative approach using a case study design, involving the boarding school leader, administrators, and students selected through purposive sampling. Data were collected through observation, interviews, and documentation, with data validity ensured through source and technique triangulation. The findings indicate that student management is implemented systematically through three main stages: planning, implementation, and supervision. Planning includes meetings and evaluation of previous programs, setting goals and disciplinary policies, preparing work programs and student activity schedules, and assigning duties to administrators. The implementation of disciplinary development is carried out through the application of daily activity schedules, habituation of congregational worship, halaqah and religious study activities, role modeling by teachers, and the provision of educational sanctions for rule violations. Supervision is conducted directly by teachers and dormitory administrators and indirectly through case records and periodic evaluation reports, demonstrating that student management plays an important role in shaping students’ discipline.